Literature Review on Behavior to Use Digital Education Platform Based on UTAUT2 in China - Huang, Juan; Pinmanee, Saichon; Chaveesuk, Singha (My University, 2025)
New online learning, online education, and digital education have gradually become a development direction in the field of education in China. But the effect of practical learning and teaching is not ideal. This paper uses the literature review approach. The objective of this paper is to summarize the impact of technological pedagogical and content knowledge (TPACK) on willingness and behavior to use in digital education platforms. Therefore, this study introduced the knowledge framework of TPACK theory based on the Extend Unified Theory of Acceptance and Use of Technology (UTAUT2), so as to construct the continuous use intention framework of using the digital education platform for rural teachers in China. The main findings show that there is the impact, and that the findings for TPACK found in the willingness and behavior of digital education platforms do not have a holistic conceptual framework. The results showed that, based on the current situation of rural teachers using a digital education platform and employing the theories of UTAUT2 and TPACK, the study developed a theoretical model framework and proposed research hypotheses. These research results provide new ideas for the design and development of digital education platform.
Keywords: Digital education platforms; Rural teacher; TPACK ability; UTAUT2